The Mediating Role of Brand Image on Product Quality, Positioning and Price on Purchase Decision - Rahmawati, Novi; Edastama, Primasatria (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to find out why the development of camille products is very rapid as anomalous products are able to improve brand image well. The rapid development of camille products can be based on the existence of product quality, brand positioning, price perception and brand image in having an impact on purchase decisions. The approach taken in this study is a quantitative method with purposive sampling technique. The number of samples collected was 190 respondents. The data analysis technique in this study uses the Structural Equation Modeling- Partial Least Squares (SEM-PLS) method with the results of product quality, brand positioning, price perception which has an influence on brand image. Brand image has an influence on purchase decision. Purchase decisions can also be influenced either directly or indirectly by product quality, brand positioning, price perception, and brand image. So, camille products can meet consumer needs with their advantages, and make packaging that is easily recognizable by consumers.